I miss my pencil a design exploration - Bone, Martin; Johnson, Kara. (San Francisco, Calif. Chronicle, 2009)
From the Publisher: What if doorbells used smell instead of sound? What if watches told time more slowly on weekends? Designers at the ground-breaking firm IDEO the most innovative design company in the world push themselves to ask seemingly outrageous questions like these daily as they work to construct the products that shape our lives. Following 12 design experiments conceived by designers at IDEO, I Miss My Pencil takes a voyeuristic look at what designers do daily, might get to do once, and sometimes only hope to do. Each experiment is made real through collaboration, sketching, prototyping, fabrication, and photographing to go beyond the conceptual to the curiously concrete.
Introduction -- 12 Experiments -- What does a laptop taste like? -- Aisthetika -- Experiment 1: Ink -- Do sheep dream of electric printers? -- Experiment 2: Blow -- I'll huff and I'll puff and I'll cool your house down! -- Experiment 3: Smellbell -- I'm getting a hint of postman and lavender -- Experiment 4: Loop -- Knife, fork, spoon, nose -- How the knitting became cool -- Punk manufacturing -- Experiment 5: Pixelated -- Saint Peter wished he had this one -- Experiment 6: Trademark -- What if manufacturing's steel toe met craft's soft underbelly in a dark alley? -- Experiment 7: Scuff -- Composition in rail slides, eggshells, and empty pools -- Experiment 8: Photo copy -- Brought to you by the letters C, A, and D -- Julie Andrews made me do it -- Love + fetish -- Experiment 9: Screw cork -- Shall I compare thee to a Bordeaux's cork? -- Experiment 10: Hebbendingetje -- I gave my heart and she gave me a pen -- Experiment 11: C60 -- 10cc's of vinyl mix, summer '09 -- Experiment 12: Black -- Little black dress, for gentlemen -- Conclusion.
Keywords: Bone, Martin; Johnson, Kara; IDEO (Firm); Industrial designers -- United States; Industrial design -- United States; Design services -- United States; New products -- United States; Creative ability; Technological innovations -- United States; Industrial design